Online Gambling Among Students - Sintia Nurizan Putri; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
Gambling is becoming a common phenomenon in daily life, particularly among children who have been exposed to mobile devices through online learning. Online gambling has become a habit even after the shift to face-to-face learning, leading to addiction among students. This study employs a review of social behavior to identify the causes of online gambling addiction in children at Rejai Middle School using qualitative research with a descriptive design. The results reveal that self-desire is a major factor causing addiction, with students seeking to acquire chips that can be exchanged for money to alleviate boredom. Socialization agents also play a role, with students influenced by peers who win and receive benefits from online gambling, and feel inferior when they do not participate. Mass media also contributes to addiction, with online advertisements and information available through the internet. Environmental factors, such as access to online gambling facilities and lack of monitoring, and family factors, such as parents' lack of monitoring and siblings' participation, also contribute to addiction. The loose school factor also impacts addiction, as schools do not strictly prohibit access to online gaming.